SIPSENIŃ (KOCHIA SCOPARIA L. SCHRAD) BİO-EKOLOGIYALÍQ ÓZGESHELIKLERI - Baltabaev, M.T.; Jabbarbergenov, A. (SCIENCE and SOCIETY, 2023)
The article presents the bioecological characteristics of the broom (kochia scoparia l. schrad). Considering that the broom has not been studied in the conditions of Karakalpakstan and the practical significance of the plant, its bioecological properties were studied under cultural conditions. The growing season of the plant begins in early April, blooms in May, bears fruit and completes the development cycle in June. Thus, it was concluded that broom (Kochia scoparia L. Schrad) can be used as feed.